Waqf Substantial Contribution Toward the Public Healthcare Sector in the Ottoman Empire - Iskandar Iskandar; Dadang Irsyamuddin; Esa Dwiyan; Hidayatul Ihsan (University of Darussalam Gontor Press, 2023)
Health is conclusively proven as an essential element in sustainable development. The great civilization unexceptionally has excellent environmental health issues as physical and mental care is fundamental to human development. In the peak period of the Ottoman Empire, public healthcare was significantly implemented by the waqf fund as an alternative to hospital financial support. Sulaymaniye complex was an example that consists of two mausoleums, two specialist schools (one of which is for the study of medicine and the other for the study of hadith), a Quranic school for children, a hospital, a hostel, a public kitchen, a public bath, an inn, and few rows of small shops. This medical school was also the introductory formal teaching workspace in the Ottoman era. However, heretofore no in-depth descriptive report on the Ottoman waqf management in the health sector is found. In fact, along with Islamic history, the government, and people both honored a collective role in the development of each appropriate instrument of waqf. This study attempts to analyze systematically the role of waqf in public healthcare facilities during the Ottoman Empire. Detailed data from books, articles, research reports, and archives were captured to support this library study.